The Problem of Forming Skills of Self-Control of Students in the Theory and Practice of Higher Professional Education - Yuliia Matviienko (Pedagogical Discourse, 2015)
The importance of using self-control in the process of learning activity of students has been shown in the article. The nature and content of self-control in learning have been chaarcterized, the state of the problem of forming self-control skills of students in the theory and practice of higherprofessional education has been analyzed and generalized. The necessity of the use of self-control of students in the learning process has been grounded. The stages of forming  knowledge and skills of the student have been described. The place of self-control in the process of learning has been determined. It is proved that development of students' abilities to independently monitor and evaluate the progress and results of their studies, allows them to manage the process of mastering knowledge, skills that enables students to gradually take over part of the educational and administrative functions of the teacher. The main stages of the research of the skills of self-control in historical terms have been examined.